2018
DOI: 10.7150/ijbs.23744
|View full text |Cite
|
Sign up to set email alerts
|

Health risks associated with genetic alterations in internal clock system by external factors

Abstract: The circadian system maintains the main aspects of physiological and behavioral processes. Both circadian rhythm and sleep impact an organism's health through interaction with environmental factors. Variations in external factors influence the functionality of clock genes and disrupt 24-hour rhythmic cycle. The disrupted circadian rhythm and disregulated sleep affect an organism's health, thereby causing several disorders including cancer, depression and cardiac disorders. Considering the role of clock genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 84 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…Lifestyle plays a huge role in disrupting circadian rhythms and therefore predisposing individuals to developing cardiovascular diseases. Desynchronization of the circadian rhythm can occur if individuals have irregular sleeping patterns or have a jet setting lifestyle with frequent flying, constantly working in changing shift patterns and being exposed to different light–dark environments, which leads to an increased risk of developing neurological disorders and cardiovascular disease (Khan et al, 2018). Per1 and Per2 shift faster compared to Clock when an individual is phase shifting and causes disruption of the circadian clock (Khan et al, 2018).…”
Section: Approaches Related To Environmental Risk Factors and “Chronomentioning
confidence: 99%
See 2 more Smart Citations
“…Lifestyle plays a huge role in disrupting circadian rhythms and therefore predisposing individuals to developing cardiovascular diseases. Desynchronization of the circadian rhythm can occur if individuals have irregular sleeping patterns or have a jet setting lifestyle with frequent flying, constantly working in changing shift patterns and being exposed to different light–dark environments, which leads to an increased risk of developing neurological disorders and cardiovascular disease (Khan et al, 2018). Per1 and Per2 shift faster compared to Clock when an individual is phase shifting and causes disruption of the circadian clock (Khan et al, 2018).…”
Section: Approaches Related To Environmental Risk Factors and “Chronomentioning
confidence: 99%
“…Desynchronization of the circadian rhythm can occur if individuals have irregular sleeping patterns or have a jet setting lifestyle with frequent flying, constantly working in changing shift patterns and being exposed to different light–dark environments, which leads to an increased risk of developing neurological disorders and cardiovascular disease (Khan et al, 2018). Per1 and Per2 shift faster compared to Clock when an individual is phase shifting and causes disruption of the circadian clock (Khan et al, 2018). Mutations in genes such as Bmal1 , Cry1 , Cry2 , Rora , and Clock can alter sleep patterns (Ko & Takahashi, 2006).…”
Section: Approaches Related To Environmental Risk Factors and “Chronomentioning
confidence: 99%
See 1 more Smart Citation
“…As circadian disruption and desynchronization exacerbate numerous health conditions from metabolic diseases, cancers to neuropsychiatric disorders (Albrecht, ; Arble, Ramsey, Bass & Turek, ; Evans & Davidson, ; Golombek et al., ; James et al., ; Khan et al., , ; Scheer et al., ), it is important to understand the interactions and impacts that circadian dysfunction or desynchronization has on the aging process. Research in hamsters has shown that circadian disorganization resulting from a mismatch between the light‐dark cycle and the free‐running period results in severe cardiac pathologies and kidney disease (Martino et al., ).…”
Section: Understanding Circadian and Aging Interactionsmentioning
confidence: 99%
“…The circadian clock maintains daily oscillation rhythms with a 24 h periodicity in all living organisms. It responds to stimuli from external environments such as light, which affect pathological and physiological functions [7]. Several genes are associated with the circadian clock, including brain and muscle Arnt-like protein-1 (BMAL1), circadian locomotor output cycles kaput (CLOCK), period (PERs; Per1, Per2, and Per3), and cryptochromes (CRYs; Cry1 and Cry2), which form a complex network of transcription-translation feedback loops, post-translational modifications, and degradation [8,9].…”
Section: Introductionmentioning
confidence: 99%